Bina Komunikasi Wisata Desa Percut Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Effiati Juliana Hasibuan; Indra Muda; Muhathir Muhathir (Universitas Medan Area, 2022)
Percut Village is a popular tourist destination in Percut Sei Tuan District, drawing visitors from all over the country, particularly on Saturdays and Sundays. There is a culinary tour in this town that serves several varieties of fish meals that guests can choose according to their preferences. Visitors can enjoy the relaxing sea views until they approach the Malaysian border on their way to the gastronomic destination. Visitors will be transported to the gastronomic destination via free fishing boats provided by the cafÃ© owner. There is also a Fish Auction Place (TPI) in this village, which attracts inhabitants who want to buy fresh fish at a low price compared to other localities. The other issue is that local folks' ability to communicate in order to entice tourists to return is still restricted. Residents' willingness to take advantage of the possibility to make things for sale is still low. Based on the dedication shown, the communication training provided to partners has proven to be very effective in promoting the various types of tourism available in Percut village, as well as the socializing provided to keep the environment clean. However, the Covid 19 epidemic, which is still rampant, has severely harmed partners' culinary businesses and fish auctions.Percut Village has tourism potential, particularly in the fields of marine tourism, beach tourism, and culinary tourism; socialization about tourism communication is very useful for opening culinary tourism visits in Percut Village; residents' understanding of environmental maintenance procedures and healthy homes is still low; and The development of Covid 19 and the imposition of Community Activity Restrictions (PPKM) had a significant impact on Percut Village's tourism appeal.